AI and Anthropology - A Path away from Disenchantment and towards Re-enchantment - Collins, Harry (2022)
This dissertation endeavours to dismantle the idea that Artificial Intelligence is a threat to our anthropology. Arguing, instead, that any such threat is a product of two main conceptual stances that we term 'Gnosticism' - a stance that entails a negative view of matter, and 'Pelagianism', a metrics-based criterion of importance. Both are argued to be erroneous when understood through the idea of the Imago Dei as our proper anthropology. Negative inferences that are thought to follow from A.I, are exposed as lacking all analytical motivation, doing so because they are ungrounded, indeed fallacious. To the contrary, A.I can be interpreted positively in relation to human flourishing, properly construed, intimating possible modes of re-enchantment.